Implementing Religious Character Education by the Teacher on Sociology Learning in SMA YPK Pontianak - Megawati, Megawati (Tanjungpura University, 2019)
This study would determine the implementation of character education of religious value by teacher in sociology learning in SMA YPK Pontianak and to find out the factors that influence the character education of religious values implementation in sociology learning in SMA YPK Pontianak. The method used in this study was descriptive method with qualitative approach. The data sources of the study were the students of grade X IIS and the sociology teacher of grade X IIS, interview and observation’s result. The results of this study showedthat the character education of religious value implementationin sociology learning involved greeting, praying before the class, the teacher implemented character education in the learning process by appreciating diversity in religion, the teacher also taught about the religious dimensions, such individuals-to-individuals, individuals to God , individuals to environment relationships, religiousservices, praying after class. Factors that influence the implementation of the character education of religious values in SMA YPK Pontianak were the religious diversity and the inadequatefacilities of worship places.